Action-FRET of β-cyclodextrin inclusion complexes. (27th January 2017) - Duez, Quentin; Knight, Geoffrey; Daly, Steven; De Winter, Julien; Halin, Emilie; MacAleese, Luke; Antoine, Rodolphe; Gerbaux, Pascal; Dugourd, Philippe
Abstract : Action-FRET is introduced as an original method to probe the structure of gaseous non-covalent complexes. Abstract : Cyclodextrin is commonly used in the formation of supramolecular complexes with an array of targets ranging from metal ion sensing to modulation of peptide properties. Many of the applications of these supramolecular complexes are measured by monitoring the modulation of the optical properties of a chromophore upon formation or breaking of the complex. The transposition of these complexes to the gas phase allows their study in a size selected manner, based on the isolation of specific stoichiometries to be analyzed independently. Förster Resonance Energy Transfer (FRET) is used to study the structure of these supramolecular complexes in solution phase. This motivates the use of action-FRET – a recently developed gas-phase extension of the FRET technique – to study the structure of gaseous supramolecular complexes. Here, the feasibility of performing action-FRET on a supramolecular assembly constituted by a chromophore tagged cyclodextrin receptor and a donor chromophore tagged amyloid beta peptide fragment is considered.